Extremely Bright, Near-IR Emitting Spontaneously Blinking Fluorophores Enable Ratiometric Multicolor Nanoscopy in Live Cells - Tyson, Jonathan; Hu, Kevin; Zheng, Shuai; Kidd, Phylicia; Dadina, Neville; Chu, Ling; Toomre, Derek; Bewersdorf, Joerg; Schepartz, Alanna (ACS central science, 2021)
New bright, photostable, emission-orthogonal fluorophores that blink without toxic additives are needed to enable multicolor, live-cell, single-molecule localization microscopy (SMLM). Here we report the design, synthesis, and biological evaluation of Yale676sb, a photostable, near-IR-emitting fluorophore that achieves these goals in the context of an exceptional quantum yield (0.59). When used alongside HMSiR, Yale676sb enables simultaneous, live-cell, two-color SMLM of two intracellular organelles (ER + mitochondria) with only a single laser and no chemical additives.